Parent and therapist perspectives on "uptime" activities and participation in Rett syndrome. Issue 24 (20th November 2022) - Buckley, Nicholas; Stahlhut, Michelle; Elefant, Cochavit; Leonard, Helen; Lotan, Meir; Downs, Jenny
Abstract: Purpose: People with a disability may spend more time sitting and lying ("downtime") and less time standing and walking ("uptime"). Caregivers and therapists supporting individuals with Rett syndrome were surveyed, aiming to gather insights on how to support participation in "uptime" activities. Method: An anonymous online survey including open ended questions about the enablers and barriers to "uptime" was administered to parent/caregivers and therapists/health professionals in an international sample. Responses were coded to the International Classification of Functioning, Health and Disability (ICF) framework identifying barriers, enablers, and strategies for increasing uptime activities. Results: Parents ( N  = 115) and therapists ( N  = 49) completed the survey. Barriers and enablers to "uptime" were identified for all ICF domains and additional data coded to enabling access to the physical environment. Strategies to promote "uptime" activities and participation particularly related to the individual's physical capacity and personal factors as well as social and physical environmental factors. Conclusions: Findings can inform the design of interventions aiming to increase "uptime" in individuals with Rett syndrome. Strategies should create individualised support by considering how to build fitness using activities that are motivating, at the same time creating opportunities for social interactions within a range of environments. IMPLICATIONS FOR REHABILITATION: "Uptime" participation comprised a dynamic interaction of "doing" the standing or walking activity, with a sense of self-engagement with the activities and interaction with others. Strategies to promote "uptime" participation should consider how to create support for person-related attributes, including building physical capacity for a greater volume of "uptime" in activities that are enjoyable and motivating. Strategies to promote "uptime participation should also include creating a supportive environment, comprising opportunities for social interaction within a range of environments".